Software copyright protection using identification key - Semenov, S. G.; Davydov, V. V. (Національний авіаційний університет, 2016)
In this work, the task of developing software copyright rights protection strategy by creating a digital ID. Protection mechanism for digital identification from replication using the information about the components of the end-user computer system is developed. Processes of creation and verification the digital identification are described. Requirements to the final software system are concluded. Disadvantages of current implementation are detected and provided.
Keywords: computer programs; software; literary works; license agreement; automatic software identification; automatic software verification